A Wide-Beam Antenna Array with Spatially-Variable-Orthogonal-Polarizations (SVOP) Achieved by Polarization-Mixing - Zeng, Fan Chao; Ding, Can; Chen, Yue-Nian; Jay Guo, Y. (IEEE transactions on antennas and propagation, 2023)
This paper introduces a novel polarization-mixing strategy to significantly widen the beamwidth of dual-linear-polarized antenna arrays without changing the array topology. Instead of using the two polarizations separately as usual, it blends the orthogonal linearly-polarized radiations to achieve wider beamwidth. The proposed method is implemented on a typical ±45°-polarized base station antenna array with its thought process and working mechanism elaborated. Much wider beamwidth is achieved compared to the traditional pattern synthesis methods based on amplitude and phase weighting or sparse arrays. The beamwidth can be controlled by simply tuning one phase shifter. Importantly, this method allows all the elements to be fully excited with the same amplitude, thus avoiding using additional amplifiers or attenuators. In the meantime, the polarization-mixing method leads to spatially-variable polarizations (SVP). To obtain polarization diversity required in cellular communication systems, two SVP arrays with the same pattern shapes are designed to have their polarizations orthogonal to each other in all directions of interest. The conditions of achieving orthogonal patterns using this method are theoretically derived and thoroughly validated in theory and in simulation. It is shown that the obtained spatially-variable-orthogonal-polarization (SVOP) arrays have a much broader beam pattern and better polarization orthogonality (PO) than that of the dual-polarized antenna element.